American Moonshot : John F. Kennedy and the Great Space Race - Brinkley, Douglas; Conkling, Winifred (New York, NY Harper, an imprint of HarperCollins Publishers, 2019)
"July 20, 1969. It's a day that has earned a spot in history. It's the day that America was the first nation to succeed in sending two astronauts--Buzz Aldrin and Neil Armstrong--to the moon. But what led to this unforgettable event? What were the stakes riding on the Apollo 11's safe landing? In acclaimed author Douglas Brinkley's first young readers' edition, space fans will get the riveting and factual backstory of arguably the most significant achievement of the 20th century."--
Includes bibliographical references (pages 257-260).
Keywords: Kennedy, John F -- 1917-1963 -- Juvenile literature. -- Influence; United States -- National Aeronautics and Space Administration -- Juvenile literature. -- History -- 20th century; Astronautics -- Juvenile literature. -- History -- 20th century -- United States; Space race -- Juvenile literature. -- United States; Space flight to the moon -- Juvenile literature. -- History -- 20th century; Astronautics and state -- Juvenile literature. -- United States; Moon -- Juvenile literature. -- Exploration -- United States